2010
DOI: 10.1080/02615470903156352
|View full text |Cite
|
Sign up to set email alerts
|

Work-based Supervisors: The Neglected Partners in Practice Learning

Abstract: The introduction of the Degree in Social Work programme in 2003 prompted considerable diversification in arrangements for practice supervision, teaching and assessment. A small scale exploratory study was undertaken into a model which utilises work-based supervisors, working in tandem with off-site practice teachers who are primarily responsible for the assessment of student social workers. The study focused on exploring the experiences of work-based supervisors and off-site practice teachers working to this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…One-to-one semi-structured interviews were used to gain understanding of participants' lived experiences of supervision, and have been used effectively in previous studies of supervision (Davys, 2005;Henderson, 2010;Tsui, 2008). Participant recruitment resulted in seven social work students participating in the research.…”
Section: Research Methodology and Designmentioning
confidence: 99%
“…One-to-one semi-structured interviews were used to gain understanding of participants' lived experiences of supervision, and have been used effectively in previous studies of supervision (Davys, 2005;Henderson, 2010;Tsui, 2008). Participant recruitment resulted in seven social work students participating in the research.…”
Section: Research Methodology and Designmentioning
confidence: 99%
“…Parker's research that explored difficulties in placement mentioned that students wanted liaison persons to be proactive in making contact and checking progress, and at times take initiative and remove them from unsafe placements (Parker, 2008). In her British study focusing on the work based supervisors of placement students, Henderson (2010) suggested that the liaison person was seen as holding expert powers, and occasionally seen as excluding work-based supervisors and not sharing sufficient information about students' past progress and history (2010). Henderson (2010) found that in placements with off-site supervision the liaison persons mainly communicated with the off-site supervisors, giving less attention to the work-based supervisors.…”
Section: The Liaison Person and Off-site Supervisionmentioning
confidence: 99%
“…In her British study focusing on the work based supervisors of placement students, Henderson (2010) suggested that the liaison person was seen as holding expert powers, and occasionally seen as excluding work-based supervisors and not sharing sufficient information about students' past progress and history (2010). Henderson (2010) found that in placements with off-site supervision the liaison persons mainly communicated with the off-site supervisors, giving less attention to the work-based supervisors. Other research exploring off-site supervision in social work placement, highlighted the importance of triad relationship and communication between the off-site supervisors, work-based supervisor and the student (Abram, Hartung, & Wernet, 2000); this USA based research did not refer to the liaison role or experience.…”
Section: The Liaison Person and Off-site Supervisionmentioning
confidence: 99%
See 2 more Smart Citations